A novel microfluidic system to separate sperm using spermatozoa inherent motion and inertial effect. (September 2022) - Ghassemi Panah, Anahita; Zabetian Targhi, Mohammad; Heydari, Ali; Halvaei, Iman
Abstract: Sperm separation is an essential part of in vitro fertilization (IVF) process. In conventional procedures, the semen sample is purified from immotile and round cells using centrifugation, which may damage sperm DNA. This study aimed to design a novel microchip to separate the progressively motile spermatozoa using a passive method instead of centrifugation. This microchip is a novel, non-invasive, and two-stage device for auto-selecting the sperm used for IVF. The first stage was designed based on lateral differentiation and rapid divergence to separate the pathways of sperm and round cells. The second stage separates high-quality sperm based on their inherent motion. Before experimenting with fresh human semen samples, preliminary tests were performed using standard particles. The results showed that at the optimized flow rate for separation (1.7 ml/h), the concentration of progressively motile spermatozoa at outlet was significantly increased compared with the initial sample.